INTELLECTUAL CAPITAL (1C) AND PROPENSITY TO MERGERS AND ACQUISITIONS (M&A) IN THE INDIAN PHARMACEUTICALS AND CHEMICAL INDUSTRY - Revathi C,; Dr. V Kavida, (The journal of contemporary issues in business and government, 2022)
This study is intended to analyse the various Intellectual Capital(IC) components and other firm specific factors which determines the M&A decision of a firm in the Indian pharmaceutical and chemical industry. Binary logistic regression is used for testing the various Intellectual Capital components such as Human Capital(HC), Structural capital (SC) and Customer capital(CC) and firm characteristics like Firm size, Leverage and Return on Asset on propensity to M&A in these high tech industries. The result shows that IC elements, namely, HC, SC, and CC are the strong determinant of M&A propensity in the pharmaceuticals and chemicals industry in India. In the pharmaceutical industry, the companies which are having less HC (labour intensity) and high SC( R&D and patent ) and strong CC( Marketing & distribution Intensity) are more tend to go for M&A. And acquirers in the pharmaceutical industry are larger in size, and their firm performance also good. In the chemical industry, the companies that have higher HC, higher Innovation Capital and higher CC and less experienced companies have more probability of an acquirer. Similar to pharmaceutical acquirers, these acquirers are also larger in size, and they have better firm performance.